Fermented Mucilage from Theobroma cacao L. Pods for Weed Control Through Allelopathy - Ramos-Remache, Rommel Arturo; Reyes-Pérez, Juan José; Macias-Macias, Ramón Antonio; Macías-Pettao, Ramón Klever; Arcos-Palma, Yordy Ariel; Espinosa-Palomeque, Bernardo (REVISTA TERRA LATINOAMERICANA, 2025)
Weeds play an important role in ecological systems due to their rapid growth, high adaptability, and invasive nature. In agricultural systems, their management constitutes a fundamental practice within the set of cultural operations, along with pruning, shade regulation, and pest control, as it directly af fects the yield of Theobroma cacao L. (cacao) crops. The objective of this study was to determine the ef ficacy, severity, and phytotoxicity of fermented mucilage from cacao fruits, considering its allelopathic potential as a herbicidal agent for weed control in cacao plantations. Six treatments were applied: T1 (1 day), T2 (30 days), T3 (60 days), T4 (90 days), T5 (5 years), and a control (water), using a randomized complete block design with four replications. The bromatological properties of each treatment were previously characterized. Weed control indicators such as ef ficacy, severity, and phytotoxicity were evaluated five and ten days af ter application. The treatment with fermented mucilage for five years (T5), with an acetic acid content of 6.37%, showed the greatest ef fectiveness in weed control. This treatment had a dif ferentiated impact on grasses and dicotyledons, being more ef fective against the latter. High phytotoxicity was observed in species such as Portulaca oleracea (purslane), which exhibited total desiccation of the foliage, and Rottboellia exaltata L. (cocoa vine), which showed complete wilting of the plant. These results suggest that the use of cacao mucilage with prolonged fermentation periods may represent a sustainable and selective alternative for weed management, particularly against broadleaf species, in cacao production systems.